2015
DOI: 10.1007/s10902-015-9668-y
|View full text |Cite
|
Sign up to set email alerts
|

Second Wave Positive Psychology: Exploring the Positive–Negative Dialectics of Wellbeing

Abstract: Positive psychology has tended to be defined in terms of a concern with 'positive' psychological qualities and states. However, critics of the field have highlighted various problems inherent in classifying phenomena as either 'positive' or 'negative.' For instance, ostensibly positive qualities (e.g., optimism) can sometimes be detrimental to wellbeing, whereas apparently negative processes (like anxiety) may at times be conducive to it. As such, over recent years, a more nuanced 'second wave' of positive psy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
165
0
16

Year Published

2016
2016
2023
2023

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 244 publications
(200 citation statements)
references
References 63 publications
4
165
0
16
Order By: Relevance
“…Indeed, all capture the notion that flourishing is dialectical, a complex blend of light and dark elements (Lomas & Ivtzan, 2015), as reflected in the Chinese symbol yin-yang (陰陽). Separately, yin means cloudy/overcast, and yang 'in the sun' (i.e., shone upon), and together these imply the two sides of a mountain (one sunlit, one in shadow).…”
Section: Complex Feelingsmentioning
confidence: 99%
“…Indeed, all capture the notion that flourishing is dialectical, a complex blend of light and dark elements (Lomas & Ivtzan, 2015), as reflected in the Chinese symbol yin-yang (陰陽). Separately, yin means cloudy/overcast, and yang 'in the sun' (i.e., shone upon), and together these imply the two sides of a mountain (one sunlit, one in shadow).…”
Section: Complex Feelingsmentioning
confidence: 99%
“…For instance, a study by Ruini et al (2003) showed that well-being scores did not strongly predict psychological distress scores in healthy adults, and vice-versa. Thus, well-being and distress are not incompatible and can coexist (Lomas and Ivtzan 2015).…”
Section: Mbis and Positive Psychologymentioning
confidence: 99%
“…It furthermore often implied that the former were necessarily good, and should be sought, whereas the latter were intrinsically bad, and should be eschewed. However, in recent years, a 'second wave' of the field has been emerging (Held, 2004;Wong, 2011;Lomas & Ivtzan, 2015), in which it is recognised that: (a) ostensibly positive states can be detrimental to wellbeing in certain circumstances, e.g., 'excessive optimism' is linked to health risk behaviours (Weinstein, 1987); (b) apparently negative states can sometimes be conducive to flourishing, e.g., anxiety can alert us to potential threats, and encourage pro-active coping (Norem, 2001); and, (c) many desirable states (e.g., love) are actually 'co-valenced,' involving a complex dialectical blend of light and dark elements (Lazarus, 2003). In this context, perhaps the current paper can contribute towards a re-appraisal of boredom, challenging the conventional view that it is necessarily 'negative' and devoid of value, and suggesting that it has the potential, if engaged with, to be a positive and rewarding experience.…”
Section: Analysis and Discussionmentioning
confidence: 99%